(untitled) (Oratio Directa, 2019)
This study examines press workers' political involvement, welfare pressures, and struggles for journalistic professionalism through the public sphere. It aims to understand the lifeworld of mass media workers and the role of Kedai Kopi Perjoeangan Jakarta as a journalists' public sphere for deliberative democracy. The study employed a qualitative approach using snowball sampling, non-participant observation, and documentation. The data were interpreted through Habermasian hermeneutics. The findings show that the coffee shop provides a communication space where press workers discuss political pressures, welfare, ethics, and professional rights. These discussions build participation and shared aspirations, although communication may be either rational or strategic. The venue therefore operates both as a deliberative arena and as a site for organizing press workers' professional demands.